The dynamics of disability and the rehabilitative potential in osteoarthrosis of the extremity joints - Yaremenko, Dmytro; Shevchenko, Olena; Golubeva, Inna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
On the basis of the analysis of disability in 3,383 patients with their joint pathology and the detailed expert analysis of 88 cases of disability caused by osteoarthrosis of the extremity joints, peculiarities were found in the disability dynamics for the above pathology, as well as the rehabilitative potential and rehabilitative prognosis were determined depending upon the kind and character of the provided medical rehabilitation and with consideration of disability criteria for patients with osteoarthrosis of large joints at different age.